2022
DOI: 10.1002/adfm.202212367
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Synapse Based on Oxygen Vacancy Migration in Ferroelectric‐Like C‐Axis‐Aligned Crystalline InGaSnO Semiconductor Thin‐Film Transistors for Highly Integrated Neuromorphic Electronics

Abstract: Artificial synapses are a key component of neuromorphic computing systems. To achieve high‐performance neuromorphic computing ability, a huge number of artificial synapses should be integrated because the human brain has a huge number of synapses (≈1015). In this study, a coplanar synaptic, thin‐film transistor (TFT) made of c‐axis‐aligned crystalline indium gallium tin oxide (CAAC–IGTO) is developed. The electrical characteristics of the biological synapses such as inhibitory postsynaptic current (IPSC), pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 82 publications
(116 reference statements)
4
13
0
Order By: Relevance
“…[35,36] The crystallization of amorphous IGTO (a-IGTO) increases the ratio of oxygen vacancy (V o /(M-O + V o + M-OH)) from 13.5% to 32.8%. [8,9,34] It can be confirmed by analyzing the X-ray photoelectron spectroscopy (XPS) O1s intensity spectra deconvoluted into three Gaussian peaks of metal-oxygen bonds (529.9 ± 0.2 eV), oxygen vacancy (530.9 ± 0.2 eV), and oxygen-hydroxyl group (531.6 ± 0.1 eV) respectively as reported previously. [34,37] The optical bandgaps of a-IGTO and CAAC-IGTO thin films by Tauc' plot are 3.78 and 3.81 eV, respectively.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…[35,36] The crystallization of amorphous IGTO (a-IGTO) increases the ratio of oxygen vacancy (V o /(M-O + V o + M-OH)) from 13.5% to 32.8%. [8,9,34] It can be confirmed by analyzing the X-ray photoelectron spectroscopy (XPS) O1s intensity spectra deconvoluted into three Gaussian peaks of metal-oxygen bonds (529.9 ± 0.2 eV), oxygen vacancy (530.9 ± 0.2 eV), and oxygen-hydroxyl group (531.6 ± 0.1 eV) respectively as reported previously. [34,37] The optical bandgaps of a-IGTO and CAAC-IGTO thin films by Tauc' plot are 3.78 and 3.81 eV, respectively.…”
Section: Resultssupporting
confidence: 79%
“…Further details of the crystallization process are described in the experimental section. According to our previous work, [34] we confirmed that the metal cations are aligned to the c-axis after crystallization by measuring both X-ray diffraction intensity peak at 2𝜃 = 31°and transmission electron microscopy image of the IGTO thin film. [35,36] The crystallization of amorphous IGTO (a-IGTO) increases the ratio of oxygen vacancy (V o /(M-O + V o + M-OH)) from 13.5% to 32.8%.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations